PENERAPAN METODE EVERYONE IS A TEACHER HERE DALAM MENINGKATKAN MINAT BELAJAR DI SMAN 14 MAROS - M, Syamsinar; Wahab, Abdul; Ahmad; Bunyamin, Andi; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ interest and learning outcomes in Islamic Religious Education through the implementation of the Everyone Is a Teacher Here method in class XII Kumer 3 at SMAN 14 Maros. This research employed Classroom Action Research (CAR) conducted in two cycles, namely Cycle I and Cycle II, each consisting of planning, action, observation, and reflection stages. The research subjects were 32 students. Data were collected through observation, interviews, tests, and documentation, and analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in students’ interest and learning outcomes in each cycle. In the pre-cycle stage, learning mastery was only 37.5% with an average score of 50.62. After the implementation of the method in Cycle I, mastery increased to 56.25%. Furthermore, in Cycle II, learning mastery significantly improved to 87.5% with an average score of 84.53. In addition, students demonstrated increased activeness, confidence, and participation in the learning process. Therefore, the Everyone Is a Teacher Here method is effective in improving students’ interest and learning outcomes.